Correlation between echocardiographic parameters of left ventricle and glycosylated hemoglobin in children with type 1 Diabetes Mellitus - ESANU, Valeriu; PALII, Ina (One Health & Risk Management, 2022)
Introduction. Deterioration of left ventricular (LV) parameters in Diabetes Mellitus (DM) can occur in the absence of other heart problems. An association between glycosylated hemoglobin (HbA1c) and changes of the LV parameters in DM has been reported. However, data regarding this association model in children with Type 1 Diabetes Mellitus (T1DM) are limited. The purpose of the work was to investigate the association between HbA1c and the LV parameters in pediatric patients. Material and methods. The study was conducted on 28 children with T1DM ((aged 10 - 18 years, gender M (15)/F (13), duration ≥5 years). The clinical (standard medical examination) and paraclinical (biochemical dosage – HbA1c, echocardiography – LV functional and structural parameters) data was carried out. Statistical analysis used the SPSS version 20. Results. The correlational study between the HbA1c and the LV parameters revealed a statistically significant positive correlation coefficient with aortic root diameter (mm) (r=0.7**, p<0.001), left atrium (mm) (r=0.8**, p<0.001 LV diastolic diameter (mm) (r=0.7**, p<0.001), LV systolic diameter (mm) (r=0.7**, p<0.001), septal wall thickness (mm) (r=0.5*, p=0.036), posterior wall thickness (mm) (r=0.5*, p=0.032), LV diastolic volume (ml) (r=0.5*, p=0.025), LV systolic volume (ml) (r=0.6**, p=0.01), ejection fraction (%) (r=0.7**, p=0.001), fractional shortening (%) (r=0.6**, p=0.002). Conclusions. The results of the study show that in children with T1DM, the increase value of the HbA1c is associated with a consensual and proportional increase in the values of the parameters of the left ventricle.